Development of motivational self-regulation in childhood—An integrative review - Maike Trautner; Martin Pinquart (Frontiers in Psychology)
Motivational self-regulation is an important skill supporting task engagement, achievement, and wellbeing during learning and other potentially strenuous tasks. It refers to active thoughts and behaviors used to initiate or maintain one's task engagement by manipulating underlying motivational processes (Wolters, 2003). This involves knowledge about one's own motivation and task characteristics, motivational control strategies, as well as monitoring of motivational processes. Most research on motivation regulation has focused on adolescents and adults; but little is known about motivation regulation in pre- and primary school children and its development. The present integrative review therefore analyzes theoretical accounts of motivation regulation to identify components of the process which may develop during childhood. To draw tentative hypotheses on how the complex process develops during childhood, it reviews research on the development in related areas of self-regulation, for example, self-regulated learning and emotion regulation. Drawing on this, it poses questions for future research on assessment methods, the development of metamotivational knowledge, monitoring, and control, as well as factors influencing their development.